Understanding the Relationships between Trauma and Criminogenic Risk Using the Risk-Need-Responsivity Model. Issue 3 (16th March 2021) - Fritzon, Katarina; Miller, Sarah; Bargh, Danielle; Hollows, Kerrilee; Osborne, Allana; Howlett, Anna
ABSTRACT: Despite the high rates of trauma histories in offenders and the link between trauma and subsequent criminal behavior, the mechanisms underlying the relationship between trauma and criminogenic risk factors have not received adequate attention. Trauma-informed care is increasingly a priority in forensic organizations, although individual trauma work is rarely a focus for prison-based intervention. Research conducted with female offenders has consistently found higher rates of complex trauma histories in comparison to male offenders. Current correctional models are disproportionately informed by studies of male offenders despite findings of disparities between offending pathways based on gender and histories of complex trauma. A review of the literature regarding the relationship between trauma and offending behavior using the Risk-Need-Responsivity (RNR) model of criminogenic needs and the relationship between trauma and offending in females in comparison to males is considered. Findings have both pragmatic and theoretical significance for addressing the gap in exploring etiological mechanisms linking the RNR criminogenic risk factors to crime. Implications and recommendations for correctional policy and model development addressing trauma will be discussed.